The Bright but Right View? New Evidence on Entrepreneurial Optimism - Ola Bengtsson; Daniel Ekeblom (Lund University, School of Economics and Management, Department of Economics, 2014)
Existing empirical evidence suggest that entrepreneurs are optimists, a finding researchers often interpret as evidence of a behavioral bias in entrepreneurial decision-making. We revisit this claim by analyzing an unusually large survey dataset (180,814 responses) that allows us to create a good measure of entrepreneurial optimism. Our measure is based on the individual's beliefs about nationwide future economic conditions. These beliefs form a good measure of optimism because they, unlike an individual's beliefs about her own future economic conditions, are completely uncorrelated with the individual's own life or work situation (which is not optimism). Our data highlight the importance of measuring optimism correctly. About half of the survey respondents differ in their beliefs about nationwide and own conditions. In addition to its conceptual and empirical relevance, our measure of optimism makes it possible to relate an individual's beliefs to actual outcomes. We can thereby test, in a novel way, whether entrepreneurial optimism is a behavioral bias or not. We first show that entrepreneurs have more favorable beliefs about nationwide conditions. We then show that these entrepreneurs' beliefs are relatively good predictors of the future. We conclude from these two findings that entrepreneurs are less biased towards optimism than non-entrepreneurs are biased towards pessimism. Additional evidence pertaining to education, which arguably correlates positively with rational decision-making, supports this conclusion. We show that entrepreneurs are more educated and their beliefs about the future are more similar to educated peoples' beliefs. In summary, our paper documents that entrepreneurial optimism is an important real-world phenomenon, yet, it may not be a behavioral bias that gives rise to irrational decision-making.
Keywords: C83; D84; E27; L26; 330; Entrepreneurship; forecast; optimism; survey data